2012
DOI: 10.1016/j.acvd.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular diseases and psychosocial factors at work

Abstract: Besides the 'classic' cardiovascular risk factors (high blood pressure, dyslipidaemia, metabolic syndrome and diabetes), the work environment is playing an increasingly significant role in cardiovascular morbidity and mortality. Several elements contribute to the effect of the work environment: physical factors, chemical factors, shift work and psychosocial factors. The effects of psychosocial factors on the aetiology and progression of cardiovascular disease have been confirmed by several studies. Identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
1
13
0
1
Order By: Relevance
“…Our results are consistent with previous prospective studies of high job strain and cardiovascular disease, [8][9][10][11][12][13] metabolic syndrome components, [14][15][16] and prevalent metabolic syndrome, 17 but conflict with a cross-sectional study. 18 One study of job strain and metabolic syndrome observed individuals in the Whitehall II cohort of civil service workers in England for 14 years.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are consistent with previous prospective studies of high job strain and cardiovascular disease, [8][9][10][11][12][13] metabolic syndrome components, [14][15][16] and prevalent metabolic syndrome, 17 but conflict with a cross-sectional study. 18 One study of job strain and metabolic syndrome observed individuals in the Whitehall II cohort of civil service workers in England for 14 years.…”
Section: Discussionsupporting
confidence: 89%
“…Prospective studies link high-strain jobs to cardiovascular disease and diabetes [8][9][10][11][12][13] and to individual components of metabolic syndrome, such as hypertension. [14][15][16] Nevertheless, there are few published studies on the association between job strain and metabolic syndrome, particularly in the United States.…”
mentioning
confidence: 99%
“…3 Hypertension has been associated with occupational psychosocial stress, especially among men. 26 However, job strain was not associated with stroke among men with hypertension at baseline. Hence, the present study indicates that stroke has a different pattern of risk factors compared with CHD.…”
Section: Methodological Considerationsmentioning
confidence: 97%
“…Furthermore, the job demand-control model has been criticized for being more valid for men, with generally larger effect sizes or effects only present in men. 20,22 Thus, this could explain why we only found associations between job strain and PD in high-educated men.…”
Section: Discussionmentioning
confidence: 86%